2020
DOI: 10.3329/bjb.v49i1.49095
|View full text |Cite
|
Sign up to set email alerts
|

Management of fusarium wilt of tomato by botanicals and biocontrol agents and their effect on yield

Abstract: Investigation was undertaken to screen out the extract of botanicals viz., neem leaf, neem oil, garlic, marsh paper plant, allamanda leaf, wood apple leaf, betel leaf and biological antagonists viz., Trichoderma viride and T. harzianum. Positive control was soil amendment with Provax and negative control with untreated soil. Soil drenching with Provax and untreated soil showed 7.65 and 37.5% wilt of tomato. Wilt incidence varied from 8.5 - 30.81%. Botanicals and biocontrol agents had significant effect on yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(5 reference statements)
2
2
0
Order By: Relevance
“…Hosen & Shamsi (2019) also found significant antifungal activity using Allium sativum (53.85%), Ocimum sanctum (48.72%) and Zingiber officinale (49.35%) against Fusarium solani and F. oxysporum. Our current results were also supported by data from Khatun et al (2020) and Kareem & Al-Araji (2017). In our present study, Coccinia grandis plant leave extract showed a promising MIC capability to control Fusarium concentricum fungus.…”
Section: Discussionsupporting
confidence: 91%
“…Hosen & Shamsi (2019) also found significant antifungal activity using Allium sativum (53.85%), Ocimum sanctum (48.72%) and Zingiber officinale (49.35%) against Fusarium solani and F. oxysporum. Our current results were also supported by data from Khatun et al (2020) and Kareem & Al-Araji (2017). In our present study, Coccinia grandis plant leave extract showed a promising MIC capability to control Fusarium concentricum fungus.…”
Section: Discussionsupporting
confidence: 91%
“…Hosen & Shamsi (2019) also found significant antifungal activity using Allium sativum (53.85%), Ocimum sanctum (48.72%) and Zingiber officinale (49.35%) against Fusarium solani and F. oxysporum. Our current results were also supported by data from Khatun et al (2020) and Kareem & Al-Araji (2017). Confirmation of the potential of antagonists on the radial growth of the pathogen in dual culture have been previously reported by Akhtar et al (2010).…”
Section: Discussionsupporting
confidence: 91%
“…(2020), 13 garlic extract gave the highest yield (29.66 t/ha) which was statistically identical to positive control (30.55 t/ha). Other treatments also showed better performance in increasing yield and suppressing Fusarium wilt of tomato.…”
Section: Resultsmentioning
confidence: 63%